Formative Assessment and Self-Regulated Learning during Pandemic Era - Ai Fatmawati; Pupung Purnawarman; Didi Sukyadi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
During online learning in Covid-19 outbreak, self-regulation is needed more due to the different learning situation and distance between student and teacher. One of the ways to support student self-regulated learning in EFL classes is through the implementation of formative assessment. The aim of this study is to find out the formative assessment that EFL teachers use in online learning and how they perceive the role of formative assessment in supporting students’ self-regulated learning. To get the data, questionnaire adapted from Gan et al. (2019); Pat-El et al. (2013) was utilized. Interviews also were conducted to get deeper understanding about the findings obtained through questionnaire. The findings revealed that during online learning, EFL teachers used a variety of formative assessment techniques, using online platforms that were easy to use. They agreed that students need to have self-regulated learning skills during online learning. However, some of them did not know for sure that the formative assessment they conducted could enhance students’ self-regulated learning since only some students submitted their work. Further research can be done to find out strategies to implement formative assessment using technologies or tools utilized in online learning where the students can get immediate feedback and use it to help them improve their learning.